The organization of attention in typical development: A new preschool attention test battery. (23rd November 2012) - Breckenridge, Kate; Braddick, Oliver; Atkinson, Janette
Abstract : This article introduces a new battery of attention tests for typically developing and atypically developing children with a mental age of 3–6 years. In the light of adult and child studies supporting a model of distinct networks for specific attentional operations, tests in the current battery were selected with the aim of measuring functions of selective attention, sustained attention and attentional control (executive function). Normative data were collected from 154 typically developing children aged 3–6 years and examined using exploratory factor analysis to determine latent constructs underlying test performance. This analysis suggested increasing differentiation of attention functions over the age range, with support for the hypothesized three‐factor model only after 4½ years of age. Additional analyses supported the validity of the new attention battery with respect to (1) parent/teacher report measures of everyday attention behaviour and (2) later performance on the Test of Everyday Attention for Children (TEA‐Ch), a battery designed for children aged 6–16 years. The results show the developing differentiation of attention functions and support the ecological and predictive validity of the battery as providing early performance‐based measures of attention and an attention 'profile' for each individual child, which may aid characterization and remediation of neurodevelopmental disorders.